Spontaneous Resolution of Migrated Peritoneal Dialysis Catheter - Asheesh Kumar; Ram Singh; Dheeraj Sharma; Samriti Gupta (Indian Journal of Kidney Diseases)
Catheter migration is defined as a displacement of the catheter tip from the pelvis to the abdomen above the posterior border (sacral promontory) of the pelvic brim on the abdominal-pelvic radiograph. Catheter migration is common and results in peritoneal dialysis failure, but not all migrated catheters are problematic. Spontaneous resolution of a migrated catheter is rare. We report a case of spontaneous resolution of the migrated tip catheter.